Reimagining Venom Harvesting: Practical Electrostimulation on Vespa velutina Nest in Nature - Xesús Feás; Daniel J. Cabadas; Carmen Vidal (Diversity)
The growing interest in Vespa velutina venom stems primarily from its impact on human health due to stings and its potential pharmacological applications. Traditionally, venom extraction methods have relied on capturing individual hornets or removing and euthanizing entire nests, followed by dissection of venom sacs—a labor-intensive and disruptive process. In this work, we present a novel, non-invasive approach to venom harvesting. Using a portable electrostimulation device, venom was extracted directly from active Vespa velutina nests in their natural habitat. This method eliminates the need for nest manipulation, significantly reducing disturbance and improving efficiency. These visuals highlight the practicality and potential of this groundbreaking technique, opening new avenues for sustainable and scalable venom collection.